Micromechanics of substrate-supported thin films - He, Wei; Han, Meidong; Wang, Shibin; Li, Lin-An; Xue, Xiuli (Acta mechanica Sinica, 2018)
The mechanical properties of metallic thin films deposited on a substrate play a crucial role in the performance of micro/nano-electromechanical systems (MEMS/NEMS) and flexible electronics. This article reviews ongoing study on the mechanics of substrate-supported thin films, with emphasis on the experimental characterization techniques, such as the rule of mixture and X-ray tensile testing. In particular, the determination of interfacial adhesion energy, film deformation, elastic properties and Bauschinger effect are discussed.